On (Not) Being Milton: Tony Harrison’s Liminal Voice - Handley, Agata G. (Text Matters: A Journal of Literature, Theory and Culture, 2016)
Tony Harrison’s poetry is rooted in the experience of a man who came out of the working class of Leeds and who, avowedly, became a poet and a stranger to his own community. As Harrison duly noted in one interview, from the moment he began his formal education at Leeds Grammar School, he has never felt fully at home in either the world of literature or the world of his working class background, preferring to continually transgress their boundaries and be subject to perpetual change. The paper examines the relation between poetic identity, whose ongoing construction remains one of the most persistently reoccurring themes of Harrison’s work, and the liminal position occupied by the speaker of Harrison’s verse. In the context of the sociological thought of such scholars as Zygmunt Bauman and Stuart Hall, the following paper discusses the way in which the idea of being in-between operates in “On Not Being Milton,” an initial poem from Harrison’s widely acclaimed sonnet sequence The School of Eloquence, whose unique character stems partly from the fact that it constitutes an ongoing poetic project which has continued from 1978 onwards, reflecting the social and cultural changes of contemporary Britain.